THE INFLUENCE OF THE OPEN ENVIRONMENT ON THE DEVELOPMENT OF CREATIVE THINKING SKILLS IN CHILDREN AGED 5-6 YEARS AT RA NURUL ISTIQOMAH - Sakdia, Kholifatus; DP, Terza Travelancya; Ali, Mahfudz (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study aims to determine the influence of the open environment on the development of creative thinking in children aged 5-6 years at RA Nurul Istiqomah. Nature-based learning environments provide hands-on experience through interaction with real objects, so that they can stimulate children's curiosity, imagination, and ability to explore new ideas. The method used in this study is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The study subjects were group B children who participated in open environment learning activities. The study results show that activities such as playing in nature, using natural materials in learning, and exploring the surrounding environment directly can improve children's ability to think divergently, solve problems, and come up with original ideas. In addition, teachers also play an important role in facilitating and directing children's activities to remain under learning goals. These findings reinforce the importance of an open-environment learning approach as an effective strategy for supporting the development of creative thinking in early childhood.